NEW CANDIDATE GENES FOR SUSCEPTIBILITY TO TUBERCULOSIS IDENTIFIED THROUGH THE CONSTRUCTION AND ANALYSIS OF ASSOCIATIVE NETWORKS - Ye. Yu. Bragina; A. A. Rudko; Ye. S. Tiys; V. A. Ivanisenko; M. B. Freidin (Бюллетень сибирской медицины, 2015)
Tuberculosis (TB) is a common disease caused by infection of Mycobacterium tuberculosis and influenced by host hereditary and environmental factors. Accumulated genomic data obtained through the use of new methodological approaches, including analysis of associative networks, contribute to the understanding of the hereditary basis of the disease. In the current study, we carried out the reconstruction and analysis of associative network representing molecular genetic links between proteins/genes involved in the development of TB. In the associative network, well studied proteins and genes with a decisive importance in the efficiency of the human immune response against a pathogen predominated. However, this approach identified 12 new genes encoding for the respective proteins in the associative network polymorphismsof which has not been studied regarding the development of TB.